A Denture Use Model Associated with Candida spp. in Immunocompetent Male and Female Rats - Sakima, Vinicius Tatsuyuji [UNESP]; Vega-Chacón, Yuliana [UNESP]; Cerri, Paulo Sergio [UNESP]; Shokeen, Bhumika; Lux, Renate; Mima, Ewerton Garcia de Oliveira [UNESP] (MDPI, 2022)
Denture stomatitis (DS) is a common infection in denture wearers, especially women. This study evaluated the induction of DS using acrylic devices attached to the palate of rats combined with inoculation of Candida spp. Immunocompetent male and female rats received a carbohydraterich diet. Impressions were taken from the rats’ palate to individually fabricate acrylic devices. Mono-and multispecies biofilms of C. albicans, C. glabrata, and C. tropicalis were grown on the devices, which were then cemented on posterior teeth and kept in the rats’ palate for four weeks. Microbial samples from the palate and the device were quantified. Oral microbiome of rats inoculated with C. albicans was analyzed by 16S rRNA gene sequencing. Log10(CFU/mL) were analyzed by mixed or two-way MANOVA (α = 0.05). Candida spp. and acrylic device did not induce palatal inflammation macroscopically nor microscopically. Although there was an increase (p < 0.001) of the total microbiota and female rats demonstrated higher (p = 0.007) recovery of Candida spp. from the palate, the gender differences were not biologically relevant. The microbiome results indicate an increase in inflammatory microbiota and reduction in health-associated micro-organisms. Although Candida spp. and acrylic device did not induce DS in immunocompetent rats, the shift in microbiota may precede manifestation of inflammation.
Keywords: Candida albicans; Candida glabrata; Candida tropicalis; dentures; oral candidiasis; rats